Optimalisasi Peran Peer Group dalam Pencegahan Kekerasan pada Anak di Masa Pandemi Covid 19 di Kabupaten Sintang - Rika Yuanita Pratama; Wagiran Wagiran (STIKes Surya Global Yogyakarta, 2022)
ABSTRACT Background of Study : As an illustration, based on SNPHAR 2018, 7% of children have experienced sexual violence, 57,14% of children have experienced emotional violence, and 25% of children have experienced physical violence. During this pandemic, children are one of the vulnerable groups and household conditions are also vulnerable. This is because many family members have to stay at home for a long time. Not to mention the economic problems due to loss of income and other problems. Methods : This study uses a Quasi Experimental research design with a pre experiment approach, the planning used is One Group Pre test and Post Test. The samples taken were 200 children aged 12 – 18 years. The sampling method in this study used proportional random sampling. The data collection method used a questionnaire before and after being given peer group facilitation. The statistical test used a paired T-test with α = 0,05. Results : The results showed that there were changes in the knowledge and attitude of preventing violence in children before and after being given peer group facilitation with the mean before being given peer group facilitation was 60,20 and 51,25, while the mean after being given peer group facilitation was 72,80 and 60,40. The results of the paired T-test analysis obtained a significant value of p value = 0,0001 = 0,05, meaning that there was an influence of peer group facilitation on the prevention of violence against children during the Covid-19 pandemic in Sintang Regency. Conclusion : Optimizing the role of peer groups can prevent acts of violence against children.Keywords : Peer groups, Child Violence